2022
DOI: 10.3390/pathogens11121476
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Influenza A Virus in Dromedaries in North-Western Nigeria

Abstract: Although influenza A virus is endemic in wild waterfowl, domestic poultry, swine, humans, bats, cetaceans, dogs, and horses, there is a paucity of data on the potential role of camels in zoonotic transmission of the virus. To estimate the seroprevalence of the influenza A virus in camel populations, four local government areas of Nigeria that share an international border with the Niger Republic were selected. Blood samples from 184 one-hump camels (dromedaries) were collected and tested for influenza IgG anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The OpenFlu and GenBank databases had limited molecular data from Nigeria. Although intermittent outbreaks were reported during this period [30], few sequences were deposited from Nigeria. The data obtained from OpenFlu for the phylogenetic analysis of the H5N1 subtype showed more cases reported in Africa after the 2006 outbreak in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OpenFlu and GenBank databases had limited molecular data from Nigeria. Although intermittent outbreaks were reported during this period [30], few sequences were deposited from Nigeria. The data obtained from OpenFlu for the phylogenetic analysis of the H5N1 subtype showed more cases reported in Africa after the 2006 outbreak in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Nigeria will continue to experience an increased burden of avian influenza due to three major wild bird migratory routes that transverse the country from Asia and Europe, coinciding with the yearly peak periods of AIV outbreaks [29]. Secondly, the presence of migratory bird sanctuaries, especially in northern Nigeria [30], serves as a point for the introduction of novel strains of AIV, as observed during the 2015-2016 epizootics. Overall, Nigeria will still be a hotspot for AIV epizootics, which will subsequently spread to other regions of Africa, and this has been revealed by the clades that are circulating in other African countries.…”
Section: Discussionmentioning
confidence: 99%
“…A vast majority of camels in Nigeria are raised extensively, where they are exposed to extrinsic environmental factors suitable for vector proliferation. Recent studies have highlighted a predisposition of camels to zoonotic pathogens such as influenza A virus [ 29 ], MERS-CoV [ 30 ], Rift Valley fever virus [ 31 ], and hepatitis E virus [ 32 ]. CCHFV is an arboviral infection that can be categorized under acute undifferentiated febrile illness (AFI) in humans with unspecified clinical manifestations ranging from fever, headache, and malaise [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against pdmH1N1 and H3N2 were also detected in camels in Nigeria in 2015-2017 [332]. Several serosurvey studies in camels in African countries confirmed the presence of antibodies against influenza A, B, C, and D [336][337][338][339][340]. α2,3-SA are abundant in the camel nasal respiratory epithelium and in the sub-epithelial regions, in the secretory goblet cells of the nasal epithelium, and in alveolar epithelial cells [341].…”
Section: Camelsmentioning
confidence: 99%